ANALISIS KEBERLANJUTAN PENGELOLAAN PERUSAHAAN DAERAH AIR MINUM TIRTA SIAK KOTA PEKANBARU - Bayu Eka Utama; Bintal Amin; Sofia Anita (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
In Indonesia, almost all clean water supply for the community is carried out by the government-owned drinking water company, namely the Regional Drinking Water Company (PDAM) and is directly under the auspices of the city government. For Pekanbaru City, the provision of clean water services is carried out by the Regional Owned Enterprises, Regional Drinking Water Company (PDAM) Tirta Siak which is under the auspices of the Pekanbaru City Government. . Until now PDAM Tirta Siak still has problems relating to the amount of drinking water production. Clean water management by PDAM Tirta Siak Pekanbaru City has various problems. These problems include technical and non-technical problems. However, problems often occur due to the condition of the water source itself, often the condition of water quality, quantity and continuity is unstable. Water management problems occur due to many factors that influence it. The purpose of this study was to determine the status of the sustainability of the Tirta Siak Regional Drinking Water Company in Pekanbaru City based on 3 dimensions, namely ecology, economy and social. The analytical method uses a multi-disciplinary rapid assessment with MDS (Multidimensional Scaling) analysis. The results of the analysis show that the sustainability index value in the ecological dimension is 53.6% with a fairly continuous status where the sensitive factor is water availability, the economic dimension is 50.9% with a fairly continuous status where the sensitive attribute is collection effectiveness, while the social dimension is 49.9% with status less sustainable where the sensitive attribute is the employee training ratio.